A lógica do espectro: romance histórico, necromancia e o lugar do morto - Almeida, Marcos Vinícius Lima de (2018)
Under the premise that our history is constituted under the impact of catastrophes, and that in this context, writing a historical novel will never be a neutral gesture, this paper proposes to investigate the historical novel in contemporary Brazilian fiction, from the perspective of theory and literary creation. This work proposes a hypothesis for the hypothesis of the hypothesis of Lukács (2011), Jameson (2007), Perry Anderson (2007), Linda Hutcheon (1991), Esteves (2010) and Weinhardt (2011) and Bastos (2007). the reading of the contemporary historical novel. From two key notions, 1) what will be defined in this work as a spectrum logic, 2) and writing as a burial rite, the central premise of this work is to look at history as a fundamentally necromantic practice. These notions are tested, or developed, from the critical reading of two contemporary works: O marechal de costas, by José Luiz Passos (2016) and De mim já nem se lembra, by Luiz Ruffato (2015). If the sign (sema) is a tomb and the writing of history and the relationship with the past is a kind of burial rite (as Jeanne-Marie Gagnebin asserts, in the wake of Michel de Certeau), which separates the past from the present world of the living dead of the world), the past not properly elaborated, not buried, returns as specter: and haunts and defiles the present. In this sense, it is possible to read the contemporary historical novel as a kind of attempt to burial the specters of the past that haunt the present. In the practical section, this work presents a novel, a historical fiction, freely inspired by the figure of Januário Garcia Leal